2016
DOI: 10.1007/s10897-016-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Preliminary Efficacy of an Internet Support Group for Parents of a Child with Neurofibromatosis Type 1: a Pilot Study

Abstract: This pilot study investigated the feasibility and preliminary efficacy of an Internet Support Group (ISG) for parents of children with NF1. Eligible parents were recruited by email and completed baseline questionnaires assessing social support, self-efficacy, depression, and anxiety. The ISG involved eight weekly 90-min chat sessions and a discussion forum open 24 h/day for 8 weeks. Follow-up measures were completed immediately post-intervention and 3 months later. Parents from 33 families (29 mothers, 4 fathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(47 reference statements)
1
12
0
1
Order By: Relevance
“…Several technologies may be involved, such as email (Bragadóttir, 2008), Facebook parent group (Campbell et al, 2016;Gruver et al, 2016), chat rooms, forums, blogs, or discussion boards (Ewing et al, 2009;Martin et al, 2016). The common feature is that these groups are always mediated by a psychologist or a health professional that monitors the adequacy of messages and information and provides additional information or feedback when appropriate.…”
Section: Online Discussion Chat Rooms and Forumsmentioning
confidence: 99%
“…Several technologies may be involved, such as email (Bragadóttir, 2008), Facebook parent group (Campbell et al, 2016;Gruver et al, 2016), chat rooms, forums, blogs, or discussion boards (Ewing et al, 2009;Martin et al, 2016). The common feature is that these groups are always mediated by a psychologist or a health professional that monitors the adequacy of messages and information and provides additional information or feedback when appropriate.…”
Section: Online Discussion Chat Rooms and Forumsmentioning
confidence: 99%
“…Assim, os cuidadores podem buscar interações online para suprir a "Carência de apoio presencial", minimizar sentimentos de solidão, entre outros fatores Stewart et al, 2011). Porém, em outra perspectiva, experiências na plataforma que acarretam "Sentimentos negativos" associadas a uma baixa "Utilidade percebida do grupo online" podem diminuir a "Participação em grupos online" Martin et al, 2014).…”
Section: Relações Entre As Variáveisunclassified
“…Despite the major role parents play in their children's lives and development (Akre & Suris, 2014;Oris et al, 2015), few interventional studies have included parents/caregivers of adolescents with any CC (Shilling et al, 2013), and fewer still with NF1. A pilot interventional study has tested the feasibility of an online chat-room support group for parents of children with NF1, which appeared to have potential as an efficacious method of providing support to parents (Martin et al, 2017). Published peer-support interventions that have included parents have aimed at creating a community of parents (Ainbinder et al, 1998;Law, King, Stewart, & King, 2001;Solomon, Pistrang, & Barker, 2001), allowed parents to share their experience as caregivers (Ainbinder et al, 1998;Kerr & McIntosh, 2000;Kingsnorth, Gall, Beayni, & Rigby, 2011), or to learn from the experiences of others (Ainbinder et al, 1998;Kingsnorth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, these have largely included parents of children not adolescents (Martin et al, 2017), and those with disabilities, not somatic diseases. In particular, research has shown that social-emotional needs of youth with NF1 and their families can be addressed through internet-delivered interventions (Martin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%